Standalone Photovoltaic Power Stabilizer Using Double Series Connected Converter in Sudden Cloud Condition - Delfianti, Rezi; Mustaqim, Bima; Afif, Yusrizal (International Journal of Integrated Engineering, 2023)
Renewable energy is clean energy that cannot harm the environment in its way, especially on standalone photovoltaic electricity generation. The only problem with renewable energy electricity generation is the intermittency and its instability in power quality and power efficiency. Power system stability in renewable energy is essential during the real environmental case problem such as the sudden cloud. The sudden cloud, known for its ability to decrease solar irradiance input, depends on how thick and big the cloud is. Several attempts had been tried to increase renewable energy power system stability, including modifying its maximum power point tracker with a new algorithm such as perturb and observe. This paper discussed an improved way of maintaining renewable energy power system stability using perturb and observe Algorithm in a double series-connected Converter as the current and power stabilizer. The results show that the current overshoot has decreased by 65,336%, and the current sudden cloud undershoot decreased by 10,529%. Power overshoot also decreased by 43,685%, and the power of sudden cloud undershoot has decreased by 7,133%.